Effects of medical graphic narratives (patient comic) on Patient Reported Outcome Measures (PROMs) in patients undergoing coronary angiography and PCI. (14th October 2021) - Brand, A; Gao, L; Dreger, H; Hamann, A; Crayen, C; Brand, H; Squier, S M; Stangl, K; Kendel, F; Stangl, V
Abstract: Background/Introduction: Increasing evidence suggests that patients scheduled for invasive cardiac procedures such as coronary angiography / PCI feel insufficiently informed about the planned procedure. Purpose: To improve the Patient Informed Consent (IC) before coronary angiography by using "medical graphic narratives" (patient comic) that illustrate central IC-related aspects in a simple and understandable manner. Methods: A patient comic illustrating central steps of the procedure, risks, treatment alternatives and behavioural measures was created in collaboration with professional scientific visual communicators. In a randomised, controlled, prospective trial, we included 121 patients undergoing coronary angiography/PCI. Patients were randomised to a group that was informed about the procedure using the usual Patient IC approach (official consent form and conversation with physician; Control group) or a group that additionally obtained a patient comic for reading (graphic illustrations of central IC aspects based on the official consent form; Comic group). Patient Reported Outcome Measures (PROMs), i.e. satisfaction with and perceived quality of the patient IC, were tested in both groups comparing single items of the Client Satisfaction Questionnaire-8 (CSQ-8) and self-designed single items in both IC groups. Differences were compared using the Fisher's exact test. A p-value <0.05 was considered statistically significant. Results: PROMs showed significant benefits in favour of the Comic group: Quality of the patient IC was perceived to be "very good" in 45.0% of the Comic group compared to 24.9% of patients in the Control group (p=0.023). Only 23.0% of the patients in the Control group, compared to 40.0% in the Comic group, stated that the IC procedure completely met their expectations (p=0.012). 57.4% in the Control group and 76.7% in the Comic group stated that all of their questions were satisfactorily adressed before the procedure (p=0.015). 43.3% in the Comic group, in contrast to 18.0% in the Control group, declared to feel "very satisfied" with the obtained IC procedure (p=0.002). The acceptance of the patient comic was very high: no patient (0%) expressed feelings of not being taken seriously by reading the patient comic. Conclusions: Our data confirm pronounced limitations of the usual Patient IC practice before coronary angiography. The use of a patient comic that narratively illustrates central steps of the procedure positively impacts on patient-centered endpoints and significantly improves the patient IC procedure. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Friede Springer Herz Stiftung